The Clinical Significance of Increased Serum Proinflammatory Cytokines, C-Reactive Protein, and Erythrocyte Sedimentation Rate in Patients with Hidradenitis Suppurativa - D. Jiménez-Gallo; R. de la Varga-Martínez; L. Ossorio-García; C. Albarrán-Planelles; C. Rodríguez; M. Linares-Barrios (Hindawi Limited, 2017)
Objectives. To assess inflammatory serum markers including serum proinflammatory cytokines, C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR) according to the clinical inflammatory activity of patients with hidradenitis suppurativa (HS). Patients and Methods. Seventy-four patients with HS were studied based on the Hidradenitis Suppurativa-Physician Global Assessment (HS-PGA) score and Hurley staging system. Proinflammatory cytokines were measured using a multiplex cytokine assay. Twenty-two healthy volunteers were recruited. Results. Serum interleukin- (IL-) 6, IL-23, soluble tumour necrosis factor alpha (TNF-α) receptor I (sTNF-RI), CRP, and ESR were different in the patients with HS compared with those in the healthy controls (P<0.05). The levels of IL-1β, IL-6, IL-8, IL-10, IL-12p70, IL-17A, sTNF-RII, CRP, and ESR were significantly elevated according to inflammatory activity based on HS-PGA scores (r>0.25, P<0.05). The levels of IL-6 (r=0.53, P<0.001), CRP (r=0.54, P<0.001), and ESR (r=0.60, P<0.001) were especially well correlated with clinical inflammatory activity based on HS-PGA scores. The levels of IL-6, IL-8, sTNF-RI, sTNF-RII, CRP, and ESR were significantly elevated according to Hurley staging system. Conclusions. Serum proinflammatory cytokines, CRP, and ESR are increased in relation to the clinical inflammatory activity of patients with HS compared with healthy controls. Serum IL-6, CRP, and ESR are effective biomarkers for evaluating the severity of HS.